Is Doppler tissue velocity during early left ventricular filling preload independent?. Issue 4 (1st April 2002) - Yalçin, F; Kaftan, A; Muderrisoğlu, H; Korkmaz, M E; Flachskampf, F; Garcia, M; Thomas, J D
Abstract : Background: Transmitral Doppler flow indices are used to evaluate diastolic function. Recently, velocities measured by Doppler tissue imaging have been used as an index of left ventricular relaxation. Objective: To determine whether Doppler tissue velocities are influenced by alterations in preload. Methods: Left ventricular preload was altered in 17 patients (all men, mean (SD) age, 49 (8) years) during echocardiographic measurements of left ventricular end diastolic volume, maximum left atrial area, peak early Doppler filling velocity, and left ventricular myocardial velocities during early filling. Preload altering manoeuvres included Trendelenberg (stage 1), reverse Trendelenberg (stage 2), and amyl nitrate (stage 3). Systolic blood pressure was measured at each stage. Results: In comparison with baseline, left ventricular end diastolic volume (p = 0.001), left atrial area (p = 0.003), peak early mitral Doppler filling velocity (p = 0.01), and systolic blood pressures (p = 0.001) were all changed by preload altering manoeuvres. Only left ventricular myocardial velocity during early filling remained unchanged by these manoeuvres. Conclusions: In contrast to standard transmitral Doppler filling indices, Doppler tissue early diastolic velocities are not significantly affected by physiological manoeuvres that alter preload. Thus Doppler tissue velocities during early left ventricular diastole may provide a better index of diastolic function in cardiac patients by providing a preload independent assessment of left ventricular filling.